PENGELOLAAN EKOWISATA BERBASIS MASYARAKAT DI NEGERI HUTUMURI KOTA AMBON - Lelloltery, Henderina -; Sitanala, Merlin Renny (Universitas Pattimura, 2023)
Hutumuri Country is one of the coastal areas making Hutumuri Country has good natural resource potential, and good community resource potential for the development of community-based ecotourism. Community-based ecotourism (community based ecotourism) is a more specific form of ecotourism in which local communities have control over development and management so that they gain many benefits both economically, educationally, socially, culturally, healthily as well as benefits to the conservation of the natural environment from the development of community-based ecotourism. . Community service activities are carried out in the form of outreach or outreach to provide information to the public. The stages of implementing PKM activities include information gathering, preparation, implementation, Focus grub discussion, monitoring and evaluation. Community-based ecotourism provides space for the community to be directly involved in all tourism activities. The people of Negeri Hutumuri responded well to counseling related to community-based ecotourism and hoped that this PKM activity would continue until the formation of a tourism group in Negeri Hutumuri.